Addressing the unmet clinical need for low-volume assays in early diagnosis of pancreatic cancer - Sheik, Daniel A.; Byers, Kaleb; Thomas, Mini; Rajesh, Ummadisetti Chinna; Ifuku, Kelli; Kirkwood, Kimberly; Al-Haddad, Mohammed; Craik, Charles S.; Davisson, V. Jo (Frontiers in Gastroenterology, 2023)
Incidental detection of pancreatic cysts, a window to early detection of pancreatic cancer, is increasingly driven by an aging population and improvements in imaging technology. Classification of pancreatic cystic precursors currently relies on imaging and cyst fluid evaluations including cytology, and protein and genomic analyses. However, there are persistent limitations that obstruct the accuracy and quality of information for clinicians, including the limited volume of the complex, often acellular, and proteinaceous milieu that comprises pancreatic cyst fluid. Due to constraints of currently available clinical assays, subjective and inconsistent application of diagnostic tools by clinicians leads to unnecessary surgery and missed pancreatic cancers. Herein, we describe the pathway towards pancreatic cyst classification and diagnosis, the volume requirements for several clinically available diagnostic tools, and some of the analytical and diagnostic limitations for each assay. Then we will discuss current and future work on novel markers and methods, and how to expand the utility of clinical pancreatic cyst fluid samples. Results of ongoing studies suggest that 50 µL of pancreatic cyst fluid is sufficient to accurately rule-out non-mucinous pancreatic cysts with no malignant potential from further evaluation. It is expected that this process will leave sufficient fluid to analyze a follow-up, rule-in panel of markers currently in development that can stratify grade of dysplasia in mucinous pancreatic cysts and improve clinical decision-making.